Kecenderungan Medium Promosi Bagi Pelajar Kolej Komuniti Kota Marudu Sabah - Munir Matlin; Ahmad Sobri; Mazlin Gumbayan (Journal of Applied Accounting And Business, 2023)
Introducing the educational services offered by Kota Marudu Community College Sabah (KKKMS) to the general public requires an effective promotional approach. However, as a government higher education institution, the implementation of promotions must optimize financial resources sensibly and ensure that information reaches the intended target audience. Therefore, the purpose of this study is to identify the most effective promotional mediums for KKKMS in disseminating information and reasons for students to enroll in KKKMS. This study also aims to identify the preferred promotional mediums for KKKMS and the students' interest in obtaining information about the educational services offered by the college. This research was conducted quantitatively with 74 KKKMS students using a questionnaire. The collected data were analyzed using Microsoft Excel software. The results of this study indicate differences between the types of effective promotional mediums for KKKMS in spreading information to prospective students, compared to the students' preference for promotional mediums they are interested in to obtain information about the college. Therefore, the College's Communication and Corporate Relations Unit (UKK) is expected to enhance the management quality of the unit in terms of promotional implementation methods through more effective mediums, to publicize the offered services to the target audience, and align UKK's finances by selecting more effective advertising platforms so that the implemented promotional approach can enhance the increasing student enrollment rate in the present time